The knowledge produced through student drawings - Hatisaru, Vesife (Frontiers in Psychology, 2022)
Drawings have been extensively used as a research method to gather data from research participants including school students regarding their perceptions of mathematics and its teaching and learning. What is valued in drawing-based research in mathematics education, and what kind of knowledge is produced through student drawings, however, is not known. This study examines drawing-based research studies to understand these questions by applying a novel framework – the legitimation code theory (LCT). The study focuses on two cases: one of which looked at middle school students’ images of mathematicians (draw a mathematician) and the other examined the same age group students’ descriptions of mathematics classrooms (draw a mathematics classroom). Within both studies, greater emphases are on the students’ perceptions relating to the discipline-related issues such as teaching and learning of mathematics, mathematics classroom experiences, and practices and tools of mathematicians. Students’ perceptions of the mathematics discipline and their attitudes toward mathematics and perceptions of the attributes of mathematicians are also a focus. The study offers the LCT approach to critically analyze the drawing-based research in the mathematics education field to contribute to the production of significant and needed knowledge in the field.